HUBUNGAN KEIKUTSERTAAN KELAS IBU HAMIL DENGAN PERSIAPAN MENGHADAPI PERSALINAN DI FASILITAS KESEHATAN WILAYAH KERJA PUSKESMAS KOTAKALER SUMEDANG - Hernawati, Yeti; Zakiah, Meylina Nurul (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
The implementation of prenatal classes and the Childbirth Planning and Complication Prevention Program (P4K) aims to reduce maternal and child mortality. The implementation of prenatal classes at the Kotakaler Health Center has not yet reached the target. The achievement of the implementation of prenatal classes in 2022 was 68%. This figure has increased compared to 2021 which was only 62% although it is still below the target of 95%. The purpose of this study was to determine the relationship between participation in prenatal classes and preparation for childbirth at health facilities in the work area of ​​the Kotakaler Health Center, Sumedang Regency. The research design was cross-sectional. The population in this study were 48 pregnant women in the third trimester. The sampling technique for this study was total sampling. Univariate and bivariate data analysis used chi-square. Pregnant women actively participated in prenatal classes as many as 27 respondents (56.3%), pregnant women were ready to face childbirth as many as 22 respondents (62.9%). The results of the bivariate analysis showed a relationship between participation in prenatal classes and preparation for childbirth at health facilities in the work area of ​​the Kotakaler Sumedang Health Center. The researcher suggests that health centers and midwives vary the implementation of prenatal classes by adding interesting activities such as games or video performances so that participants are interested and can easily understand the material and can be open to discussion and increase the number of class times in the prenatal class program so that all pregnant women can attend prenatal classes in each RW in the Kotakaler Village.